The nebula secret - Trueit, Trudi Strain (Explorer Academy, 2019)
Cruz leaves his tranquil home in Hawaii to join 23 talented kids from around the globe to train at the Explorer Academy with the world's leading scientists to become the next generation of great explorers. But for Cruz, there's more at stake. No sooner has he arrived at the Academy than he discovers that his family has a mysterious past with the organization that could jeopardize his future. In the midst of codebreaking and cool classes, new friends and augmented-reality expeditions, Cruz must tackle the biggest question of all: Who is out to get him ... and why?.